Development of an Adaptive Visual-Hybrid Learning Model Based on Universal Design for Learning to Improve the Self-Regulated Learning of Deaf Students in Special Senior High School - Fidiyanti Fidiyanti; Mohammad Syaifuddin; Abdulkadir Rahardjanto (International Journal of Social Sciences and Humanities, 2026)
Self-regulated learning (SRL) is important for deaf students because upper secondary education requires greater independence in planning, monitoring, and evaluating learning. This pilot study developed and tested an adaptive visual-hybrid learning model grounded in Universal Design for Learning (UDL) for deaf students at SLB Negeri Kota Metro. A quasi-experimental nonequivalent control group design was used with 11 students in experimental and control classes. The intervention combined visual supports, captioned and text-based materials, flexible online-offline access, accessible task pathways, and guided self-monitoring activities. Data were collected through an SRL questionnaire, classroom observation, and documentation. The experimental group showed higher improvement than the control group, with mean scores increasing from 62.45 to 82.30 compared with 63.10 to 71.25. The gain scores were 0.53 and 0.22, respectively, and the independent-samples t-test indicated a statistically significant between-group difference (t = 4.87, p < 0.05). The findings suggest that visually accessible hybrid instruction aligned with UDL may support stronger SRL among deaf learners in this setting.